Doppler Shift Effect at The Communication Systems with 10 GHz around Building - Andrita Ceriana Eska (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2020)
This research described the Doppler shift effect for the communication systems. The mobile station moves with various velocities around the building’s environment. Doppler’s shift influences the communication systems. The frequency communication was used 10 GHz and its influenced by atmospheric attenuation. This research consisted of propagation with LOS and NLOS conditions, mobile station velocity variation, height buildings variation, and transmitter power variation. This research described frequency maximum at Doppler shift, coherence time, and signal to noise ratio. More increase Doppler shift of coherence time caused signal noise ratio to decrease.